Hybrid photovoltaic/conventional power system for residential use - McNicol, Finlay Henderson. (2009)
There is little doubt that human activity is contributing to global warming. Traditional fossil fuel power plants which release vast amounts of harmful gases into the atmosphere remain the backbone to electricity generation across the world. The use of clean renewable energy alternatives increases every year and will continue to do so for the foreseeable future. The cost of running traditional plants is increasing while renewable energy installations are becoming cheaper. One such renewable energy alternative is energy from sunlight, known as photovoltaics. Photovoltaics are one of the most promising renewable energy technologies in terms of potential worldwide generation. The aim of this project is to model how the conventional residential mains supply and a photovoltaic installation can be used in tandem to supply power to a single load. The model is designed in a software package. Model simulations show that with DC and AC loads the photovoltaic generated power and mains supply power are combined and delivered to a load. The efficiency of the simulated process was significantly higher with DC loads.